Lithium iron phosphate precursor, preparation method and application thereof, lithium iron phosphate positive electrode material and lithium ion battery
By preliminating lithium in the precursor of lithium iron phosphate positive electrode material, using nano-scale lithium salt cores to shorten the lithium ion diffusion path, the crystal defects and lattice stress problems caused by uneven diffusion of lithium ions in existing materials are solved, and the cycle life of the material and battery performance are significantly improved.
Patent Information
- Application Number
- CN202510004537.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
AI Technical Summary
In the existing methods for synthesis of lithium iron phosphate positive electrode materials, the lithium ion diffusion path is long, resulting in uneven diffusion, resulting in crystal defects and lattice stress, affecting the circulation life of the material.
By preliminating lithium in the lithium iron phosphate precursor and using nanoscale lithium salt as the core, the lithium ion diffusion path is shortened, the crystal growth environment is improved, and the lattice stress and defects are reduced.
The uniform distribution of lithium ions in the positive electrode material is achieved, the circulation life of the material is improved, and the capacity and efficiency of the battery are enhanced.
Smart Images

Figure CN119797298A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and specifically relates to a lithium iron phosphate precursor and a preparation method and application thereof, a lithium iron phosphate positive electrode material and a lithium ion battery. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] With the rapid growth of the number of electric vehicles, the range anxiety problem has become increasingly prominent, and the demand for lithium batteries for materials with higher energy density is increasing. Lithium iron phosphate positive electrode materials have been widely studied and applied due to their high safety and low price. However, the existing synthesis method of lithium iron phosphate positive electrode materials mainly adopts the method of solid phase sintering after the physical mixing of iron phosphate precursor with lithium source (mainly lithium carbonate) and carbon source. For example, patent CN116768176A discloses that the iron phosphate precursor is mixed with carbon source, lithium source and additives, and the positive electrode material is obtained by grinding, spray drying, sintering and crushing. During the high-temperature calcination process, the molten lithium source wraps the solid iron phosphate precursor, and the lithium ions diffuse into the iron phosphate precursor. At this time, due to the long lithium ion diffusion path and large steric hindrance, it is difficult for lithium ions to migrate into the iron phosphate precursor, and the diffusion is uneven, resulting in different degrees of defects, lattice distortion and lattice stress in the growth of the lithium iron phosphate positive electrode material crystals at the microscopic level, which will lead to particle cracking of the lithium iron phosphate positive electrode material after long-term circulation, which will have a certain impact on the capacity, efficiency, cycle life, etc. Summary of the invention
[0004] In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a lithium iron phosphate precursor and a preparation method, application, lithium iron phosphate positive electrode material and a lithium ion battery. The present invention uses a precursor pre-lithiation method to shorten the lithium ion diffusion path length in the positive electrode material production process, thereby achieving the purpose of improving the lattice stress and lattice defects of the positive electrode material, and ultimately achieving the purpose of improving the performance of the positive electrode material.
[0005] In order to achieve the above object, the technical solution of the present invention is:
[0006] The first aspect of the present invention provides a lithium iron phosphate precursor, comprising a core, an iron ion layer deposited on the surface of the core, and an iron phosphate layer deposited on the surface of the iron ion layer, wherein the core is a nanoscale lithium salt particle, and the mass fraction of lithium in the lithium iron phosphate precursor is 0.1 to 0.5%.
[0007] In the process of preparing the positive electrode material of lithium-ion batteries, lithium ions migrate to the inside of the precursor under the drive of thermal energy, usually at high temperature, but the precursor is still in a non-liquid state at this time, which will cause the lithium ions to migrate to the non-liquid precursor. It is more difficult, firstly, the migration path is long, and secondly, the steric hindrance is large. The core of the lithium iron phosphate precursor provided by the present invention is a nano-scale lithium salt. During the preparation process of the positive electrode material of lithium-ion batteries, the lithium ions in the core diffuse outward, and the external lithium ions diffuse into the inside of the precursor, thereby shortening the lithium ion migration path and ensuring that the lithium ions in the lithium iron phosphate positive electrode material are evenly distributed. The present invention pre-lithiumates the precursor from the perspective of shortening the lithium ion migration path to achieve a better grain growth environment during the calcination process, and then can improve the defects and lattice stress inside the material to a certain extent, thereby achieving the effect of improving the cycle life of the lithium iron phosphate positive electrode material.
[0008] In some embodiments of the present invention, the D50 particle size of the core is 10-50 nm, the thickness of the iron ion layer is 3-10 nm, and the D50 particle size of the lithium iron phosphate precursor is 0.5-2 μm.
[0009] In some embodiments of the present invention, the lithium salt includes but is not limited to one or more of lithium carbonate, lithium fluoride and lithium phosphate, preferably lithium phosphate.
[0010] A second aspect of the present invention provides a method for preparing the above-mentioned lithium iron phosphate precursor, characterized in that it comprises:
[0011] Prepare a nano-scale lithium salt into a suspension, add an iron salt while stirring, and adjust the pH so that the iron ions are deposited on the surface of the nano-scale lithium salt as crystal nuclei to obtain a precursor intermediate A;
[0012] Adding iron salt and phosphoric acid to the precursor intermediate A, adjusting the pH, so that the iron ions and phosphates are deposited on the surface of the precursor intermediate A in the form of iron phosphate, to obtain the precursor intermediate B;
[0013] The precursor intermediate B is grown, aged, filtered and dried to obtain a lithium iron phosphate precursor.
[0014] The invention obtains the lithium iron phosphate precursor by simple deposition, has a simple preparation method and is easy for industrial production.
[0015] In some embodiments of the present invention, the content of lithium in the suspension is 15-30 g / L, calculated as lithium element.
[0016] In some embodiments of the present invention, the D50 particle size of the nanoscale lithium salt is 10 to 50 nm.
[0017] In some embodiments of the present invention, the nanoscale lithium salt includes one or more of lithium carbonate, lithium fluoride and lithium phosphate, preferably lithium phosphate.
[0018] It should be noted that the nano-scale lithium salt is a water-insoluble or slightly water-soluble lithium salt. The water-insoluble or slightly water-soluble lithium salt is added to water and mixed to obtain a suspension, so as to provide crystal nuclei for the deposition of iron ions in the next step. If a water-soluble lithium salt is used, the suspension cannot be prepared, the iron ions have no deposition object, and the lithium iron phosphate precursor cannot be successfully prepared.
[0019] It should be noted that, during the preparation of the precursor intermediate A, in order to enhance the nucleophilic pairing of the water-insoluble or slightly water-soluble lithium salt with iron phosphate and enhance the deposition efficiency of iron phosphate on its surface, a certain concentration of iron salt solution can be slowly introduced into the suspension under high-speed stirring. The present invention does not limit the speed of the high-speed stirring, and the speed of the equipment used can be adjusted according to the actual volume of the suspension. For example, it can be 500-2000rpm,
[0020] The high-speed stirring allows the iron ions to be uniformly deposited on the surface of the nanoscale lithium salt. The stirring speed of the high-speed stirring is
[0021] In some embodiments of the present invention, during the preparation of the precursor intermediate A, the pH is adjusted to 5-9, and the thickness of the iron ions deposited on the surface of the nanoscale lithium salt is 3-10 nm.
[0022] It should be noted that the present invention limits the amount of iron salt by limiting the deposition thickness of iron ions, and the amount of iron salt added can ensure that the deposition thickness of iron ions is 3 to 10 nm.
[0023] The D50 particle size of the nano-scale lithium salt used is 10-50 nm, the thickness of the iron ions deposited on the surface of the nano-scale lithium salt is 3-10 nm, and the D50 particle size of the precursor intermediate A is 13-60 nm.
[0024] In some embodiments of the present invention, during the preparation of the precursor intermediate B, the pH is adjusted to 8-11.
[0025] In some embodiments of the present invention, in the precursor intermediate B, the molar ratio of iron element to phosphorus element is 0.96-0.97:1.
[0026] It should be noted that the present invention limits the amount of iron salt and phosphoric acid by limiting the molar ratio of iron element to phosphorus element in intermediate B. Under alkaline conditions, iron ions and phosphates are deposited on the surface of precursor intermediate A in the form of iron phosphate, thereby forming precursor intermediate B.
[0027] In some embodiments of the present invention, the preparation method includes: the precursor intermediate B is grown at 45-60°C, pH 9-11, and 500-900rpm for 5-50h, then aged at 45-60°C, 150-300rpm for 10-15h, filtered, and dried to obtain a lithium iron phosphate precursor with a D50 particle size of 0.5 to 2μm.
[0028] The third aspect of the present invention provides a use of the above-mentioned lithium iron phosphate precursor or the lithium iron phosphate precursor prepared by the above-mentioned preparation method in a lithium iron phosphate positive electrode material.
[0029] A fourth aspect of the present invention provides a lithium iron phosphate positive electrode material, which is obtained by mixing a precursor, a lithium source and a carbon source, calcining in a protective gas atmosphere, and crushing;
[0030] Wherein, the precursor is the lithium iron phosphate precursor mentioned above or the lithium iron phosphate precursor prepared by the above preparation method.
[0031] In some embodiments of the present invention, the lithium source includes one or more combinations of lithium carbonate, lithium hydroxide, lithium oxalate, lithium acetate and lithium oxide, preferably at least one of lithium carbonate and lithium hydroxide.
[0032] In some embodiments of the present invention, the carbon source comprises one or more combinations of glucose, sucrose, citric acid, starch and polyethylene glycol (PEG), preferably glucose.
[0033] In some embodiments of the present invention, after the precursor, lithium source and carbon source are mixed, the molar ratio of lithium to phosphorus is 1.01 to 1.04:1, and the amount of carbon source added is added according to the carbon content of the finished product design.
[0034] In some embodiments of the present invention, the protective gas includes nitrogen and an inert gas.
[0035] In some embodiments of the present invention, the calcination conditions are a calcination temperature of 680-770° C. and a calcination time of 9-15 hours.
[0036] In some embodiments of the present invention, the carbon content in the lithium iron phosphate positive electrode material is 1.1-1.2 wt %.
[0037] A fifth aspect of the present invention provides a lithium-ion battery comprising the above-mentioned lithium iron phosphate positive electrode material.
[0038] In some embodiments of the present invention, the lithium-ion battery is cycled 1000 times at 2.0-3.65V 1C / 1C, and the cycle retention rate is greater than or equal to 92%.
[0039] The beneficial effects of the present invention are:
[0040] The present invention optimizes the structure of the iron phosphate precursor and pre-lithiates the iron phosphate precursor from the perspective of shortening the lithium ion migration path, so as to achieve a better grain growth environment during the calcination process, and then improve the defects and lattice stress inside the material to a certain extent, thereby achieving the effect of improving the cycle life of the lithium iron phosphate positive electrode material. The lithium iron phosphate precursor provided by the present invention includes a core, an iron ion layer deposited on the surface of the core, and an iron phosphate layer deposited on the surface of the iron ion layer, the core is a nano-scale lithium salt particle, and the mass fraction of lithium in the lithium iron phosphate precursor is 0.1-0.5%. It has been verified that when the number of cycles of the all-inclusive battery prepared by the lithium iron phosphate precursor provided by the present invention is 1000, the cycle retention rate is above 92%, and compared with the comparative example, the cycle improvement is very obvious.
[0041] The method for preparing the iron phosphate precursor provided by the invention is simple, efficient and easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0043] Figure 1 The cycle retention rate of the soft-pack full battery assembled using the pre-lithium precursor prepared in Example 1, Example 2 and the comparative example of the present invention. DETAILED DESCRIPTION
[0044] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0045] The raw materials used in the present invention are not particularly limited in their sources and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0046] There is no particular restriction on the purity of all raw materials in the present invention. The present invention preferably uses analytically pure materials or materials of conventional purity used in the field of lithium ion battery separator preparation.
[0047] Example 1
[0048] A method for preparing a lithium iron phosphate positive electrode material comprises the following steps:
[0049] First, a suspension prepared from lithium phosphate with a D50 particle size of 30 nm and a lithium content of 20 g / L calculated as lithium element is introduced into a precursor reactor and fully stirred.
[0050] Under high-speed stirring, a certain concentration of iron salt solution is slowly introduced into the precursor reactor, and the pH value is adjusted to 5-9, so that the iron ions are precipitated on the surface with nano-scale lithium phosphate as crystal nuclei, thereby forming a precursor intermediate A with a core of nano-scale lithium salt and an outer layer covered with a certain thickness (6nm) of iron ion deposits. The D50 particle size of the precursor intermediate A is 36nm.
[0051] Then, the liquid containing the precursor intermediate A is transferred to another reactor, and a certain amount of iron salt solution and high-purity phosphoric acid solution are continuously introduced, and a certain amount of sodium hydroxide and ammonia water are introduced to adjust the pH value to 8-11, so that iron ions and phosphates are deposited on the surface of the intermediate in the form of iron phosphate, thereby forming the precursor intermediate B. In the obtained precursor intermediate B, the molar ratio of iron element to phosphorus element is Fe:P=0.965:1.
[0052] The above-mentioned precursor intermediate B is transferred to another reactor, grown at 45-60°C, pH 9-11, 500-900rpm for 5-50h, then aged at 45-60°C, 150-300rpm for 10-15h, filtered, and dried to obtain a lithium iron phosphate precursor with a D50 particle size of 1μm, i.e., a pre-lithium precursor, in which the mass fraction of lithium is 0.3%.
[0053] The above-mentioned pre-lithium precursor is added to pure water with a certain lithium salt and a carbon source, and mixed (the molar ratio of lithium to iron is 1.03, i.e. Li:Fe=1.03, and the amount of carbon source added is added according to the carbon content designed in the finished product) and sand-milled to a solid D50 particle size of 0.5 μm in the mixed slurry, and then spray-dried and calcined in a protective gas atmosphere (such as a nitrogen atmosphere) (725°C, calcination time 12h). After crushing, screening and demagnetization, a lithium iron phosphate positive electrode material prepared from the pre-lithium precursor is obtained, in which the carbon content is 1.15wt%.
[0054] Example 2
[0055] A preparation method of a lithium iron phosphate positive electrode material, which is different from Example 1 in that: in the suspension, the lithium content is 15g / L, calculated as lithium element, and the D50 particle size of the nano-scale lithium salt is 50nm; the thickness of the iron ion deposit in the precursor intermediate A is 3nm, and the D50 particle size of the precursor intermediate A is 53nm; the molar ratio of iron element to phosphorus element in the precursor intermediate B is Fe:P=0.97:1; the D50 particle size of the pre-lithium precursor is 1μm, and the mass fraction of lithium is 0.1%; after the pre-lithium precursor is mixed with a lithium source and a carbon source, the molar ratio of lithium to iron is 1.04. The remaining steps are consistent with Example 1.
[0056] Example 3
[0057] A method for preparing a lithium iron phosphate positive electrode material, which differs from Example 1 in that: in the suspension, the lithium content is 30 g / L, calculated as lithium element, and the D50 particle size of the nano-scale lithium salt is 10 nm; the thickness of the iron ion deposit in the precursor intermediate A is 10 nm, and the D50 particle size of the precursor intermediate A is 20 nm; the molar ratio of the iron element to the phosphorus element in the precursor intermediate B is Fe:P=0.96:1; the D50 particle size of the pre-lithium precursor is 0.5 μm, wherein the mass fraction of lithium is 0.5%; after the pre-lithium precursor is mixed with a lithium source and a carbon source, the molar ratio of lithium to iron is 1.01. The remaining steps are consistent with those of Example 1.
[0058] Comparative Example 1
[0059] A method for preparing a lithium iron phosphate positive electrode material comprises the following steps:
[0060] The iron salt solution and high-purity phosphoric acid solution are passed through a certain amount of sodium hydroxide and ammonia water for pH adjustment, and the pH value is adjusted to 8-11, so that the iron ions and phosphates are deposited in the form of iron phosphate, thereby forming an iron phosphate precursor with a D50 of 36nm. Then the liquid containing the iron phosphate precursor is transferred to another reactor, and a certain amount of iron salt solution and high-purity phosphoric acid solution are continuously passed through, and a certain amount of sodium hydroxide and ammonia water are passed through for pH adjustment, and the pH value is adjusted to 8-11, so that the iron ions and phosphates are deposited on the surface of the iron phosphate precursor in the form of iron phosphate, and grown at 45-60°C, pH9-11, 500-900rpm for 5-50h, and then aged at 45-60°C, 150-300rpm for 10-15h, filtered, and dried to obtain an iron phosphate precursor with a D50 particle size of 1μm. In the obtained iron phosphate precursor, the molar ratio of iron element to phosphorus element is Fe:P=0.965.
[0061] The iron phosphate precursor is added to pure water with a certain lithium salt and a carbon source, and mixed (the molar ratio of lithium to iron is 1.03, i.e. Li:Fe=1.03, and the amount of carbon source added is added according to the carbon content designed in the finished product) and sand-milled to a solid D50 particle size of 0.5 μm in the mixed slurry, and then spray-dried and calcined in a protective gas atmosphere (such as a nitrogen atmosphere) (725°C, calcination time 12h), and after crushing, screening and demagnetization, a lithium iron phosphate positive electrode material prepared from the iron phosphate precursor is obtained, in which the carbon content is 1.15wt%.
[0062] Comparative Example 2
[0063] A method for preparing a lithium iron phosphate positive electrode material comprises the following steps:
[0064] A more mature iron phosphate precursor with a D50 particle size of 1 μm (the molar ratio of iron to phosphorus is Fe:P=0.965) is purchased directly from the market. Then the iron phosphate precursor is added to pure water with a certain lithium salt and carbon source (wherein the molar ratio of lithium to iron is 1.03, i.e. Li:Fe=1.03, and the amount of carbon source added is added according to the carbon content designed in the finished product) and sand-ground to a solid D50 of 0.5 μm in the mixed slurry, and then spray-dried, calcined in a protective gas atmosphere (such as a nitrogen atmosphere) (725°C, calcination time 12h), and after crushing, screening and demagnetization, a lithium iron phosphate positive electrode material prepared from the iron phosphate precursor is obtained, wherein the carbon content is 1.15wt%.
[0065] Cycle performance test
[0066] Preparation of soft-pack full-electric battery: The positive electrode materials prepared in the above Examples 1-2 and Comparative Examples 1-2 are respectively used to prepare soft-pack full-electric batteries, as follows: The positive electrode material, conductive agent 1 (SP), conductive agent 2 (CNT), and binder (PVDF) are weighed according to the mass ratio of 96.5%: 1.2%: 0.3%: 2%, and the weighed positive electrode material, conductive agent 1 (SP), conductive agent 2 (CNT), and binder (PVDF) are mixed in a planetary homogenizer, and then a certain amount of N-methylpyrrolidone (NMP) is added to continue homogenization until the slurry becomes a viscous liquid with a certain fluidity (solid content of 67%). Then use a transfer coater to evenly apply the homogenized slurry to the aluminum foil, and then dry it in air at 90°C, and press the compacted density to 2.50g / cm 3 Roll-pressing is performed, and the electrode sheets are cut out according to size for later use to obtain the positive electrode sheets.
[0067] Commercial graphite is used to prepare the negative electrode plate. The mass ratio of each material is graphite: binder (SBR): CMC: SP = 96.2%: 1.8%: 1.2%: 0.8%, and the compaction is 1.60g / cm 3 Rolling is performed, and the electrode sheets are cut out according to the size for use, and the negative electrode sheets are obtained. The electrolyte is a normal commercial iron-lithium battery electrolyte, and a laminated soft-pack battery is used. At 25°C, the laminated soft-pack battery is charged and discharged at a working voltage of 2.0-3.65V and 1C / 1C cycle.
[0068] Test results such as Figure 1 shown. Figure 1 : is the cycle retention rate curve of the soft-pack battery. It can be seen from the figure that the cycle improvement of the embodiment is very obvious compared with the comparative example.
[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A lithium iron phosphate precursor, characterized in that: It comprises a core, an iron ion layer deposited on the surface of the core, and an iron phosphate layer deposited on the surface of the iron ion layer. The core is a nano-scale lithium salt particle, and the mass fraction of lithium in the lithium iron phosphate precursor is 0.1-0.5%.
2. The lithium iron phosphate precursor according to claim 1, characterized in that The D50 particle size of the inner core is 10-50 nm, the thickness of the iron ion layer is 3-10 nm, and the D50 particle size of the lithium iron phosphate precursor is 0.5-2 μm.
3. The lithium iron phosphate precursor according to claim 1, characterized in that The lithium salt includes one or more of lithium carbonate, lithium fluoride and lithium phosphate, preferably lithium phosphate.
4. A method for preparing a lithium iron phosphate precursor according to any one of claims 1 to 3, characterized in that: include: Prepare a nano-scale lithium salt into a suspension, add an iron salt while stirring, and adjust the pH so that the iron ions are deposited on the surface of the nano-scale lithium salt as crystal nuclei to obtain a precursor intermediate A; Adding iron salt and phosphoric acid to the precursor intermediate A, adjusting the pH, so that the iron ions and phosphates are deposited on the surface of the precursor intermediate A in the form of iron phosphate, to obtain the precursor intermediate B; The precursor intermediate B is grown, aged, filtered and dried to obtain a lithium iron phosphate precursor.
5. The preparation method according to claim 4, characterized in that: In the suspension, the content of lithium is 15 to 30 g / L, calculated as lithium element; Preferably, the D50 particle size of the nanoscale lithium salt is 10 to 50 nm; Preferably, the nanoscale lithium salt includes one or more of lithium carbonate, lithium fluoride and lithium phosphate, preferably lithium phosphate.
6. The preparation method according to claim 4, characterized in that: During the preparation of the precursor intermediate A, the pH is adjusted to 5-9, and the thickness of the iron ions deposited on the surface of the nanoscale lithium salt is 3-10 nm; During the preparation of the precursor intermediate B, the pH is adjusted to 8-11; Preferably, in the precursor intermediate B, the molar ratio of iron to phosphorus is 0.96-0.97:
1.
7. The preparation method according to claim 4, characterized in that: The preparation method comprises: the precursor intermediate B is grown at 45-60°C, pH 9-11, and 500-900 rpm for 5-50 hours, then aged at 45-60°C and 150-300 rpm for 10-15 hours, filtered, and dried to obtain a lithium iron phosphate precursor with a D50 particle size of 0.5 to 2 μm.
8. Use of the lithium iron phosphate precursor according to any one of claims 1 to 3 or the lithium iron phosphate precursor prepared by the preparation method according to any one of claims 4 to 8 in lithium iron phosphate positive electrode materials.
9. A lithium iron phosphate positive electrode material, characterized in that: It is obtained by mixing a precursor, a lithium source and a carbon source, calcining in a protective gas atmosphere, and then crushing; Wherein, the precursor is the lithium iron phosphate precursor described in any one of claims 1 to 3 or the lithium iron phosphate precursor prepared by the preparation method described in any one of claims 4 to 8; Preferably, the lithium source comprises one or more combinations of lithium carbonate, lithium hydroxide, lithium oxalate, lithium acetate and lithium oxide, preferably at least one of lithium carbonate and lithium hydroxide; Preferably, the carbon source comprises one or more combinations of glucose, sucrose, citric acid, starch and polyethylene glycol, preferably glucose; Preferably, after the precursor, lithium source and carbon source are mixed, the molar ratio of lithium to phosphorus is 1.01 to 1.04:1; Preferably, the calcination conditions are a calcination temperature of 680-770°C and a calcination time of 9-15h; Preferably, the carbon content in the lithium iron phosphate positive electrode material is 1.1-1.2 wt %.
10. A lithium ion battery, characterized in that: It includes the lithium iron phosphate positive electrode material according to claim 9; Preferably, the lithium-ion battery is cycled 1000 times at 2.0-3.65V 1C / 1C, and the cycle retention rate is greater than or equal to 92%.